Modeling magneto-rheological damper using neural network and simulated annealing - Mohamad Luqman, Zaki Monsarif (2013)
This thesis is study about modeling the Magneto-rheological damper using Neural Network and Simulated Annealing method. Five different values of current were used in order to modeling the MR damper, which are 0.0 ampere, 0.5 ampere, 1.0 ampere, 1.5 ampere and 2.0 ampere. In order to modeling the MR damper, the graph of simulation damper will be compared with the experimental damper. The results will get the Square Error for the simulation damper. Then, the Root Mean Square Error will be calculated to get the difference between the simulation damper and experimental damper. The results show that the lowest RMSE for the simulation damper were value 1.282457, while the highest RMSE is 13.18909. From the results also, the better current value to modeling the MR damper is using the MR damper with the lowest RMSE.